School choice and information: an experimental study on matching mechanisms - Pais, Joana (2010)
We present an experimental study where we analyze three well-known matching mechanisms—the Boston, the Gale-Shapley, and the Top Trading Cycles mechanisms—in three different informational set¬tings. Our experimental results are consistent with the theory, sug-gesting that the TTC mechanism outperforms both the Boston and the Gale-Shapley mechanisms in terms of efficiency and it is as suc¬cessful as the Gale-Shapley mechanism regarding the proportion of truthful preference revelation, whereas manipulation is stronger un¬der the Boston mechanism. In addition, even though agents are much more likely to revert to truthtelling in lack of information about the others' payoffs—ignorance may be beneficial in this context—, the TTC mechanism results less sensitive to the amount of information that participants hold. These results therefore suggest that the use of the TTC mechanism in practice is more desirable than of the others.